KINETICS OF BATCH MICROBIAL DEGRADATION OF PHENOL BY PSEUDOMONAS AERUGINOSA AND DEEP-SEA SEDIMENT BACTERIA: SCALE-UP - Syafrizal Syafrizal (Scientific Contributions Oil and Gas, 2018)
Petroleum that is produced from several oil wells produces a fluid containing a mixture of petroleum, natural gas and produced water. The produced water usually contains hazardous chemicals such as hydrocarbons, sulfides, ammonia, phenols and other heavy metals. One of the high pollutants in the water produced is phenol. Through a biodegradation process, the contents of phenolic compounds in the produced water are expected to be reduced so that it meets the quality standards of waste water for oil and gas exploration and production activities. This research is development of the results of previous studies using a bioreactor with a larger scale, namely 3 L. The degradation process of phenolic compounds is carried out in optimal conditions, namely: pH 7, temperature 300C, and selected simple media: NP (5: 1) derived from urea and NPK + 0.1% yeast extract. The results of this study indicated that P. aeruginos and bacterial consortium may degrade phenolic compounds very well, which was 5.3 times faster than the previous studies. The biodegradation percentage was 98.40% in P. aeruginosa and 99.03% in bacterial  consortium respectively. The monod kinetics model approach was successfully carried out and gave the value of parameters μMax, Km, YS/X, and μd respectively of 0.6305 hours-1, 0.0280 mg/L, 7 × 10-7 mg/L/ CFU/mL, and 0.00575 hours-1 in P. aeruginosa and 0.3272 hours-1, 0.0355 mg/L, 6.63 × 10-7 mg/L/CFU/ mL, and 0.00279 hours-1 in bacterial consortium. Based on the valuesof these parameters, P. aeruginosa has better affinity and growth.